Introducing the BMC Series SDG Editorial Board Members: Taddese Zerfu - Zerfu, Taddese Alemu (BMC, 2024)
Taddese Zerfu is a research fellow at the International Food Policy Research Institute (IFPRI), focusing on the nexus between agriculture, nutrition, and health. His research examines the impact of livestock farming and animal-source foods on maternal and child nutrition in low- and middle-income countries. Previously, Taddese worked as a clinician, researcher, and academic in Ethiopia, Kenya, South Africa, and the UK. He holds a PhD in Food Science and Nutrition from Addis Ababa University and a Master’s in Public Health from Jimma University. He completed postdoctoral fellowships at Tufts University and the African Population and Health Research Center. His work has earned several awards, including the Tore Godal Medal and the African Doctoral Dissertation Research Fellowship. He belongs to the Editorial Board of BMC Public Health.